Community Service with Activities to Instill Environmental Awareness Through Sustainable Programs as an Effort to Improve School Cleanliness - Arinie Falhah; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The KKN work program with a focus on instilling environmental awareness through sustainable programs has shown positive and sustainable results, student awareness of the importance of environmental cleanliness has increased significantly. This program is an important step in maintaining school cleanliness. Through education, waste management, routine cleaning activities, it is hoped that good habits will be formed that can be continued by all school residents. This is not only about physical cleanliness, but also about building a culture of loving the environment from an early age. Continuous support from the school and student commitment are the keys to the long-term success of this program. The location of the activity was carried out at MI TWT BODAS, Mangunjaya Village. Through this program, it is hoped that there will be an increase in student awareness of the importance of maintaining the cleanliness of the school environment. Students are expected to be more responsible for the cleanliness of the school environment, which in turn can create a healthier and more comfortable learning environment. In addition, it is hoped that with this sustainable program that efforts to clean and educate the environment will continue even though the KKN program has ended. Environmental Socialization and Education in collaboration with the Education Program of the Faculty of Public Health, Wiralodra University regarding the selection of organic and non-organic waste. Implemented for 22 6th grade elementary school students. The distribution of educational materials has succeeded in reaching all students. Students showed an increased understanding of the importance of maintaining cleanliness and the impact of a polluted environment, as shown through a post-socialization survey with the results that 90% of students understood the material presented. The socialization and education that were carried out succeeded in increasing students' awareness and understanding of the importance of maintaining a clean environment. The distribution of interesting and interactive educational materials was able to attract students' interest in learning more about environmental issues. In the implementation of education, it also provided space for students to discuss and ask questions, thus increasing their active participation in this activity.